ANALISIS PENGELOLAAN DAN AKUNTANSI DEPOSITO DALAM PERBANKAN: STUDI PADA DEPOSITO BERJANGKA, SERTIFIKAT DEPOSITO, DAN DEPOSITO ON CALL - Herna Saulinawaty Hutasoit; Jestri Sumerdi Br Nainggolan; Riska Anggita Purba; Sherlyna Simanjuntak; Hamonangan Siallagan (Komunitas Manajemen Kompetitif, 2026)
This study aims to analyze the management and accounting of various types of deposits used in banking, namely time deposits, certificates of deposit, and call deposits. This study was conducted using a qualitative descriptive approach with reference to banking literature, OJK regulations, and accounting guidelines. The results show that each type of deposit has different characteristics, recording mechanisms, and operational implications. Time deposits have the characteristic of locking funds with a fixed interest rate, certificates of deposit are transferable, providing greater liquidity flexibility, while call deposits offer withdrawal flexibility with daily negotiable interest rates. The analysis also shows that accounting aspects such as liability recognition, interest calculation, recording maturity dates, extensions, and penalties have a significant impact on the bank's funding structure, liquidity, and profitability. This study confirms that a thorough understanding of the deposit mechanisms and recording is crucial for banks in maintaining funding stability, as well as for customers in determining deposit options that suit their needs and risk profiles.